Nationality as a Diplomatic Tool: Relationship between Japan and the two Koreas and the issues surrounding Zainichi Koreans - Choi, Safa (THE HALLYM JOURNAL OF JAPANESE STUDIES, 2021)
International migration is a critical global issue. This paper explores the history of Zainichi Koreans—the largest group of immigrants in Japan—and the issues surrounding their nationality during the post-colonial and the Cold War. By using sources from diplomatic and governmental archives from the Japanese government and South Korean government, this paper demonstrates that the primary aim of deciding Zainichi Koreans’ nationality was a tool for both countries to achieve their political and diplomatic aims. Existing literature on Zainichi Koreans’ nationality has emphasized their identity; however, this paper highlights the complicated intersection between diplomacy and immigrants’ nationality. KCI Citation Count: 0